Hydrogen bonding and short contacts in [2,4,6-tris(trifluoromethyl)phenyl]phosphinic acid. - Cornet, S; Dillon, K; Howard, J; Monks, P; Thompson, A (2009)
In the title compound, C(9)H(4)F(9)O(2)P, molecules are linked by a single O-H...O hydrogen bond into chains related to those in phenylphosphinic acid. There are short intramolecular F...P contacts.